Emozioni e pedagogia. Per un primo inquadramento scientifico - Michele Cagol (Firenze University Press, 2019)
This theoretical contribution is an attempt to provide a scientific framework for the Italian studies on emotional education of the last thirty years in the light of the recent proposals of the philosophy of emotions and of some neuroscientific lines of research. The article proposes a working classification of the various pedagogical perspectives in relation to the traditions of emotion theories (What are emotions?), to the issue of universalism (Do emotion categories designate natural kinds?), and, in particular, to the nature of the link between emotion and cognition/reason.